Usefulness of a new DUV-LED device for the control of infection by Escherichia coli, Staphylococcus aureus, mycobacteria and spore-forming bacteria - Inagaki, Hiroko; Goto, Yoshitaka; Sugiyama, Hironobu; Saito, Akatsuki; Okabayashi, Tamaki; Watanabe, Kyosuke; Fujimoto, Shouichi (Frontiers in Public Health, 2022)
Reliable disinfection and sterilization technologies are needed to deal with the various infectious diseases spreading around the world. Furthermore, bacteria that are difficult to eliminate by ordinary disinfection are also a problem in the medical environment. We examined the germicidal effect of a newly developed deep-ultraviolet light-emitting diode (DUV-LED) prototype device (wavelength of 280 ± 5 nm; power of 0.9 to 1.4 mW/cm2) for floor sterilization against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Mycobacterium gordonae (M. gordonae), and Bacillus subtilis (B. subtilis). This prototype device is equipped with highly practical DUV-LEDs with a high output efficiency and a long life, and was designed with consideration of the irradiation distance and the angle of the DUV-LEDs to provide a uniform irradiation rate. We found a statistically significant reduction of ≥90% in the infectious titers of both E. coli and S. aureus after irradiation for 2 s. Although acid-fast bacilli and spore-type bacilli are generally thought to be resistant to UV light irradiation compared to general bacteria, the acid-fast bacillus M. gordonae was inactivated after irradiation for 10 s, and spore-type cells of the bacillus B. subtilis were inactivated by ≥90% after irradiation for 30 s. We also found that the effects were cumulative when irradiation was performed at intervals. In the future, the usefulness of this device as an infection control measure will be evaluated in daily medical practice.